2010
DOI: 10.2478/v10009-010-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

Internal phosphorus loading in selected lakes of the Cybina River valley

Abstract: The aim of this study was to assess the ability of bottom sediments to release or accumulate phosphorus. Ex situ experiments with the use of undisturbed sediment cores were done in 11 lakes situated in the Cybina River valley (Wielkopolska, Poland). Phosphorus release was observed both in aerobic and anaerobic conditions, however greater values were noted in the latter ones. Maximum values reached 41.4 mg m -2 d -1 P and 12.2 mg m -2 d -1 P in anaerobic and aerobic conditions, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These results coincide with the results of a study of the nutrients from Curonian Lagoon and their impact on the ecosystems of the Curonian Lagoon, which were presented on 10-01-2017 [14]. However, Kowalczewska-Madura et al [32] found that phosphorus release from sludge continues throughout the year in deeper lake areas. Slightly higher values were observed only at the beginning of summer and autumn, and the emitted phosphorus remained in the water layer near the bottom for a long time.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results coincide with the results of a study of the nutrients from Curonian Lagoon and their impact on the ecosystems of the Curonian Lagoon, which were presented on 10-01-2017 [14]. However, Kowalczewska-Madura et al [32] found that phosphorus release from sludge continues throughout the year in deeper lake areas. Slightly higher values were observed only at the beginning of summer and autumn, and the emitted phosphorus remained in the water layer near the bottom for a long time.…”
Section: Discussionsupporting
confidence: 88%
“…Factors that promote phosphorus release include temperature, pH, concentration of oxygen in the sludge and water layer above the sludge [47], redox potential, type of chemical compounds containing phosphorus, concentrations of Fe, Mn, Al and Ca [38,43,48], bioturbation by microinvertebrates [49] and structure of the bottom sediment [50]. The deposition of phosphorus from sludge to water and its transfer to the trophogenic zone may be more intense than its sorption and deposition [32].…”
Section: Discussionmentioning
confidence: 99%
“…In trying to exploit natural mechanisms of self-regulation, we make the ecosystem less prone to serious disturbance. Most data relating to the internal loading of lakes concerns shallow water bodies (e.g., Kozerski and Kleeberg 1998 ; Søndergaard et al 2001 ; Dondajewska 2008 ; Kowalczewska-Madura and Gołdyn 2009 ; Joniak and Kuczyńska-Kippen 2010 ; Kowalczewska-Madura et al 2010 ), but little is known about the release of phosphorus from deep, dimictic lakes (e.g., Kleeberg 1997 ; Murphy et al 2001 ), especially those subjected to restoration treatments (Kowalczewska-Madura et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature affects the formation and abundance of heterocysts in both Dolichospermum and Aphanizomenon [ 50 ] and is important for phosphorus and ammonia concentrations. Experimental studies conducted at 16 °C have shown that phosphorus can be released from sediments under aerobic and anaerobic conditions, and the processes were more intense under anaerobic conditions [ 51 ]. Therefore, the threshold of 16 °C for A. flos-aquae and D. planctonicum could be related to the release of phosphorus or to the ammonia concentration, which was significant in the 5% of samples dominated by A. flos-aquae .…”
Section: Discussionmentioning
confidence: 99%